Demographic situation in the regions of Ukraine as a prerequisite of labor potential formation and development - Lyudmila Melnik; Svitlana Batychenko (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
The formation of labor potential is a crucial prerequisite for the socio-economic stability of the country, and its effective use is the basis of productivity of the national economy. In the context of Ukraine's integration into the world economic space, an important task is to study the internal and external factors that influence the country’s labor potential formation. The factors of external influence include: the level of socio-economic development of the region, country; level of demographic development of the region, country; state of the national and regional labor market and conditions of labor price formation; the legal framework governing social and labor relations; social and entrepreneurial investment. The magnitude of the labor potential of the country and the region depends more on the demographic situation (total population, its structure, life expectancy, birth rate and death rate). Demographic factors mainly influence the quantitative component of labor potential. The article deals with the issues of pop-ulation dynamics in the regions of Ukraine, as well as birth rate, death rate, middle age, population reproduction. The regions of Ukraine are grouped according to the age structure of the population, and the regions with the prevalence of the share of pensioners over adolescents, the regions with the prevalence of the share of the population younger than the working age, and also the regions with the highest proportion of the working population respectively. In addition to natural population growth / decline, the population's demographic potential is affected by mechanical movement of the population, that is, features of migration processes of the population. According to the indicators of migration growth / reduction, the corresponding groups of regions of Ukraine are highlighted. At the present stage there are significant changes in the population demographic structure, which in turn caused a significant deterioration in the quantitative and qualitative status of the country's labor potential. Population reductions, high death rates and low birth rates, and a negative migration balance, indicate that the demographic situation needs a lot of attention from the state. It is extremely necessary to respond and implement appropriate measures, if not to increase the quantitative parameters of labor potential, at least to preserve the existing status. The main levers of regulation of labor potential include: increase in income and standard of living; increase in life expectancy; increase in natality; return of compatriots working abroad, etc.